1974
DOI: 10.4141/cjas74-084
|View full text |Cite
|
Sign up to set email alerts
|

A Linear Programming Model for Beef Cattle Production

Abstract: Brokken (1971a,b), McDonough (1971 and Scott and Broadbent (1972) using linear programming (LP). Optimal weights for buying and selling feedlot cattle have been considered in addition to optimal feeding programs by Meyer and Newett (1970) and Kennedy (1972)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The impact of the alternative genotypes on economic values, however, was not considered. Economic efficiency was found to depend on the genotype of animals (Wilton et al 1974;Bourdon and Brinks 1987;Lamb et al 1992), suggesting that economic values would also be affected, and this was observed here.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The impact of the alternative genotypes on economic values, however, was not considered. Economic efficiency was found to depend on the genotype of animals (Wilton et al 1974;Bourdon and Brinks 1987;Lamb et al 1992), suggesting that economic values would also be affected, and this was observed here.…”
Section: Discussionsupporting
confidence: 73%
“…The effect of alternative genotypes on economic and biological efficiency has also been previously investigated with beef production models (Wilton et al 1974;Bourdon and Brinks 1987;Lamb et al 1992). The impact of the alternative genotypes on economic values, however, was not considered.…”
Section: Discussionmentioning
confidence: 99%
“…This analysis used the basic LP model described by Wilton et al (1974) For personal use only. Morris and Wilton (1975) …”
Section: Methodsmentioning
confidence: 99%
“…More complex systems are better described by computer modelling. With beef cattle, production models have been developed primarily for comparison of breeds and crosses in different environments (Wilton et al 1974;Bourdon and Brinks 1987;Lamb et al 1992). These beef production models often have limited value for defining economic values for within-breed improvement.…”
mentioning
confidence: 99%